A Review Featuring Fabrication, Properties, and Application of Polymeric Mixed Matrix Membrane Reinforced with Different Fillers. Issue 18 (12th December 2017) - Muntha, Sedra Tul; Kausar, Ayesha; Siddiq, Muhammad
ABSTRACT: Mixed matrix membrane is composed of polymer matrix reinforced with organic or inorganic particles to improve its performance. This review presents comprehensive study on fabrication, properties, and application of polymeric composite-based mixed matrix membrane. Inorganic fillers (silica, alumina, and zeolite) are extensively used in mixed matrix membrane due to low cost, abundance, and simplistic surface treatment. Organic fillers (graphene and carbon nanotube) are also preferred due to low specific gravity, and high thermal, flame, and chemical resistance. Reinforcement of these nanofiller during membrane provides flux enhancement and low fouling. Various applications of mixed matrix membrane such as in tissue engineering, catalysis, and electrochemistry have also been discussed. GRAPHICAL ABSTRACT: